Understanding Electrical Performance and Microstructure of Water Tree Aged Cables after Silicone Injection during Electrical-Thermal Accelerated Aging. Issue 12 (21st July 2017) - Zhou, Kai; Li, Kangle; Yang, Mingliang; Huang, Ming; Li, Tianhua
Abstract: To further understand the long-term effect of rejuvenation fluid on water tree aged cross-linked polyethylene (XLPE) cables after silicone injection, electrical performance and microstructure of water tree aged cables were investigated during an electrical-thermal accelerated aging experiment. Two groups of treated and untreated water tree aged cable samples were subjected to electrical-thermal aging for 2 weeks. The results of the dielectric loss factor showed that the electrical performance of the treated samples was significantly better than that of untreated samples after electrical-thermal aging. Microobservation results showed that the overall water tree sizes of the treated samples were much smaller than those of the untreated samples after electrical-thermal aging. Furthermore, there was a second growth of water trees in the original water tree region during electrical-thermal aging in both groups of samples. Using scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS), rejuvenation fillers were observed tightly embedded in water tree voids after electrical-thermal aging. The infrared (IR) spectroscopy analysis results showed that the concentration of rejuvenation fluid increased from the outer layer to the inner layer of insulation. Based on the results, due to the improvement of the electric field at the water tree tip and the diffusion of silicone fluid in the insulation layer, both the second growth in the original water tree region and continuing growth at the water tree tip can be effectively inhibited.